PENGEMBANGAN INSTRUMEN PENGASUHAN BERBASIS NILAI BUDAYA JAWA - Etikawati, Agnes Indar; Siregar, Juke Roosjati; Jatnika, Ratna; Widjaja, Hanna (Jurnal Ilmu Keluarga dan Konsumen, 2019)
The concept of parenting cannot be separated from the context of the local culture. This study aimed to develop an instrument of parenting for Javanese families. The study was conducted using design of exploratory sequential mix method.The first step was exploration of the construct of Javanese parenting, and the second was the examination of measurement model. The exploration step was conducted using focused group discussion (FGD) involving 50 Javanese mothers and an interview involving 19 Javanese parents who live in Yogyakarta. The result of exploration step showed that the concept of Javanese parenting is built upon seven values, that are; value of respect to elder (hormat), harmony (rukun), self-control (kendali perilaku), acceptance (‘nrimo’/sikap menerima), self-discipline (disiplin), honesty (jujur), and love (tresno). Then the construct was generalized into items that can be understood by children.The measurement model examination step involved 334 fifth grade students in first trial and 175 fifth grade students on the second trial. The result of the measurement model examination showed that the Javanese parenting costruct is valid (RMESA=0.063; SRMR=0.068) and reliable (Cronbach’s alpha = 0,925). The result indicate the relevance of local cultural values in development of parenting instrument.